Work- and family-role adjustment of different types of global professionals: Scale development and validation - Shaffer, Margaret A; Sebastian Reiche, B; Dimitrova, Mihaela; Lazarova, Mila; Chen, Shoshi; Westman, Mina; Wurtz, Olivier (Journal of International Business Studies, 2016)
Although the original model of expatriate adjustment proposed by Black and colleagues has received substantial empirical support, it has come under increased academic scrutiny, due to both the conceptual overlap among its dimensions and its limited applicability for global professionals who interact with individuals from diverse cultures. Drawing on role theory, we conceptualize and develop a multidimensional scale of the work- and family-role adjustment of global professionals. We assess this scale through five interlocking studies using data from a total of 1231 corporate and self-initiated expatriates, international business travelers, and global domestics. After confirming the scale’s dimensionality, we provide evidence for convergent, discriminant, nomological, and predictive validity. We also demonstrate differences in levels of adjustment and in relationships between work and family demands and resources and their respective forms of adjustment across various types of global professionals. We contribute to international business research, and the organizational behavior and work–family literatures, by offering a theoretically based scale that assesses adjustment to both work and family roles for a wide range of global employees. Our scale further lends itself as a diagnostic tool during the selection, training, and support of global professionals and their families.